Wanita dan pengurusan emosi melalui pengkisahan Maryam dalam al-Quran - Najah Nadiah Amran,; Haziyah Hussin, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Emotion has impact on individuals’ ways of thinking and actions. It can be manifested physically and verbally. Studies indicate that male and female behaviours are dissimilars in emotional coping and reactions. Studies also underline the presence of internal and external factors, which related to stress and anxiety that can influence women’s emotions. The failure of dealing with emotional burdens and battles can be devastating as it gives negative impacts to the individuals and community’s quality of life and well-being. The aim of this article is to highlight the importance of emotional coping skill by examining the stories of women in the Quran.Verses of the Quran related to the stories of Maryam in the Quran and exegeses are compiled and analysed thematically. This article explores the personality of Maryam, the mother of Prophet Isa through the lens of life challenges and important elements and references in emotional coping. It classifies Maryam’s life into four phases starting from her infancy to motherhood. Through those phases, Maryam underwent hardships and contested with the Israilites’ tradition and challenges. This article concludes there are six important points in emotional coping skills that can empower women while dealing with life challenges and predicaments. They are: (i) stronghold of faith; (ii) consistency in religious ritual and submission; (iii) continuous efforts in purifying of soul; (iv) living in isolation or physically separating from toxic environment; (v) seeking for external moral and physical supports; and (vi) sharpening essential life skills and strategies.